Transformative Multifunction Deep Ultraviolet Photodetectors for On-Demand Applications: From Fast Optical Communication to Tunable In-Sensor Photocurrent Integration - Kumar, Mohit; Park, Hayoung; Seo, Hyungtak (ACS Applied Materials and Interfaces, 2024)
The strategic utilization of photodetectors’ transient response could open new frontiers from free-space optical communication to the emerging field of neuromorphic optoelectronics. Contrarily, while communication requires a fast response, neuromorphic applications benefit from a slow and integrative transient photocurrent. By integrating these functionalities in a single device, this study unveils a photodetector with tunable responses, bridging the gap between optical communication and neuromorphic sensing and creating a versatile platform with on-demand applications. Particularly, a Ga2O3-based photodetector was designed, exhibiting a photocurrent on/off ratio close to 104, high responsivity of 0.43 A/W, and detectivity 1.22 × 1013 Jones under deep ultraviolet illumination (λ ∼ 260 nm). The photodetector demonstrates transient time-dependent on operational voltage, ranging from 10-4 to 0.2 s. The underlying mechanism is attributed to the voltage-dependent balance between photocarrier generation and defect-related recombination, as revealed by electrostatic force microscopy. Additionally, we have demonstrated potential applications, including digital Morse code interpretation, tunable integration of optical inputs within the sensor, one-time readouts, and effective analog Morse code reading. Furthermore, the effectiveness of input information recognition using analog integration, even with anomalies, was demonstrated. This work establishes a versatile approach for tunable in-sensor optical processing, potentially useful for a wide range of applications, from free-space optical communication to neuromorphic sensing.
Keywords: Deep ultraviolet; Deep uv; Deep UV photodetector; In-sensor processing; Morse codes; Neuromorphic; On-demand applications; Sensor processing; Tunables; UV photodetectors; deep UV photodetector; in-sensor processing; integration; Morse code; optical communication